Shading and controlled-release fertilizer in the production of Oenocarpus bataua Mart. Seedlings - Araújo, James Maciel de; Rodrigues, Maria Júlia da Silva; Capistrano, Márcia da Costa; Andrade Neto, Romeu de Carvalho; Mattar, Eduardo Pacca Luna; Lunz, Aureny Maria Pereira (Comunicata Scientiae, 2023)
When associated an adequate shading and nutrition the seedlings to reach characteristics that allow them to survive in the field and increase production. Thus, this work aimed to evaluate the production of Oenocarpus bataua seedlings in response to different shade environments and controlled-release fertilizer doses. The study was carried out from at the Embrapa nursery located in the municipality of Rio Branco, Acre state. The experimental design was complete randomized blocks with three replications and six plants per plot. The treatments were distributed according to a 4 x 5 factorial scheme, i.e., four shade environments (20%, 30%, 50% and 75%) and five CRF doses (0.0, 1.5, 3.0, 4.5 and 6.0 kg m–3) mixed with the substrate. Biometric, biomass and quality variables were evaluated at 305 days after transplanting. The ANOVA was applied for the qualitative factor and regression analysis was performed for the quantitative factor, both at 5% probability. The treatments were grouped by analyzing canonical variables, a multivariate statistical and realized the Pearson’s correlation between variables was determined through correlation networks. The shading environment and the controlledrelease fertilizer positively influenced the growth and quality of Oenocarpus bataua seedlings. The seedlings of Oenocarpus bataua have better biometric characteristics produced in a nursery with 50% shading. Oenocarpus bataua seedlings show better quality when 3.88 kg m-3 of controlled release fertilizer are used.